MEMAHAMI HADIS WAKAF DALAM KONSTALASI MASYARAKAT GLOBAL (UIN Sunan Kudus, 2015)
The role of the Waqf is very strategic for the development of the muslim community throughout both concern education, health, and well-being. But the unfortunate developments that have been achieved so far are still struggling on the field of worship, education, and health alone, while the field of economics that are the pillars of modern life has not been touched wide. Many waqf property is “problematic”, as questioned by the heirs, even sued to court, there are deprived openly, no one asked back because of religious differences between expert wars with the Waqif., And some are sold expert inheritance for bankruptcy